Perbaikan Manajemen Bank Sampah Di Desa Selat Untuk Meningkatkan Nilai Tambah Pengolahan Sampah Menjadi Pupuk Organik Dengan Aplikasi Berbasis Android - Komang Gede Darmayasa; Made Putra Sedana; I Putu Prasna Mahardika; I Kadek Heri Suardan; I Dewa Gede Andreano Eldo; Nengah Taksu Yusaramana; I Nyoman Mahatma Yogeshvara; I Kadek Dhananjaya Dana Putra; Made Naradha Adithya; I Made Dwijaksana; Made Agus Putra Harta Narayana; Putu Pande Devaryana Putra; Made Rasmika Werdhi Nugraha; I Putu Gede Raditya Wikadhyana; I Dewa Gede Agung Astina Wirayudha; Made Sucipta (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The waste problem in Selat Village has caused severe environmental pollution. The main cause of this problem is because most of the people in Selat Village have not been able to carry out proper and integrated waste management, resulting in uncontrolled accumulation of waste. The general objective of this research is to initiate the progress of village areas in Indonesia regarding Waste Digitalization. The results of this study indicate that the Wita Bersih Application can shorten the time and make it easier for the Selat Village garbage bank in processing plastic waste.